KINERJA DAN FINANCIAL DISTRESS: NAVIGASI PADA BISNIS TRANSPORTASI - Asri Widyayanti, Denok; Kristianti, Ika Puspita (LPPM STIE YKPN Yogyakarta, 2024)
This study aims to explore the impact of activity ratios, profitability, and leverage on financial distress within the transportation sector. Specifically, we measure financial distress using the Springate method. Additionally, we assess activity through the Receivable Turnover Ratio (RTR), profitability via the Net Profit Margin (NPM), and leverage using the Debt to Asset Ratio (DAR). To achieve our objectives, we employed purposive sampling, selecting 25 transportation companies listed on the Indonesia Stock Exchange. Our observation period spans from 2019 to 2021, resulting in a total sample size of 75 observations. We sourced secondary data from both the Indonesia Stock Exchange and official company websites during this period. Our study adopts a quantitative research approach. Using SPSS 26 software, we processed the collected data. The analytical model employed is binary logistic regression analysis. Our testing includes descriptive statistics, hypothesis testing (partial tests, goodness of fit, overall model fit, coefficient of determination, and simultaneous effects), and assessment for multicollinearity. Partially, our results reveal significant relationships. The activity and profitability ratio negatively affects financial distress, while conversely, the leverage ratio has a significant positive effect on financial distress. Simultaneously, all three ratios—activity, profitability, and leverage—jointly influence financial distress.